Hair methylmercury levels are inversely correlated with arterial stiffness. (September 2022) - Park, Kyung-Chae; Kim, Ki Soo; Jung, Bo Sung; Yoon, Siyeong; Ahn, Wooyeol; Jeong, Simho; Choi, Junwon; Lee, Soonchul
Abstract: Background and aims: Cardiovascular diseases (CVD), including coronary heart disease, are the leading cause of death worldwide. Several studies investigating the relationship between fish intake, methylmercury exposure, and CVDs in adults have reported inconsistent results. This study aimed to determine the association between hair methylmercury levels and arterial stiffness using brachial–ankle pulse wave velocity (baPWV). Methods: This cross-sectional study included 891 seemingly healthy Korean adults (418 men and 473 women). The anthropometric and biochemical profiles, including methylmercury levels in the hair, were measured. Arterial stiffness was measured using baPWV, wherein high baPWV was defined as >1375 cm/s (>75th percentile). The odds ratios for high baPWVs were examined using multivariable logistic regression analysis after adjusting for potential confounders across the quintiles of hair methylmercury levels (Q1 = ≤0.6, Q2 = 0.6–0.8, Q3 = 0.8–1.1, Q4 = 1.1–1.5, and Q5=>1.5 μg/g). Results: After adjusting for multiple confounders-age, sex, height, body weight, smoking status, weekly alcohol consumption, total metabolic equivalent of task, mean arterial blood pressure, resting heart rate, triglycerides, low density lipoprotein cholesterol, fasting plasma glucose, uric acid and white blood cell count-the odds ratios (95% confidence intervals) for high baPWVs in each quintile of hair methylmercury levels were 1.00, 0.36 (0.17–0.76), 0.38 (0.20–0.76), 0.28 (0.13–0.61), and 0.49 (0.24–0.99), respectively. Conclusions: Within non-toxic low levels, higher hair methylmercury levels are independently associated with lower arterial stiffness in seemingly healthy Korean adults regardless of classical cardiovascular risk factors. Graphical abstract: Image 1 Highlights: Hair methylmercury levels are inversely related to brachial–ankle pulse wave velocity. Methylmercury at non-toxic low levels may demonstrate hormetic effect to cardiovascular disease. Low hair methylmercury levels are independently associated with higher arterial stiffness.